Sintered Composition

JP7633343B2Active Publication Date: 2025-02-19ALPHA ASSEMBLY SOLUTIONS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023172081
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2023-10-03
Publication Date
2025-02-19
Estimated Expiration
2040-09-24

Smart Images

  • Figure 0007633343000007
    Figure 0007633343000007
  • Figure 0007633343000008
    Figure 0007633343000008
  • Figure 0007633343000009
    Figure 0007633343000009
Patent Text Reader

Abstract

To provide a simpler and cheaper sintering composition which is more easily manufactured and which can provide an improved joint strength, and superior printed lines and circuits, and with fewer carbon impurities in the joints resulting in higher electrical and thermal conductivity.SOLUTION: A sintering composition consists essentially of: a solvent; and a metal complex dissolved in the solvent. The content of the metal complex in the sintering composition is at least 60 wt.% based on the total weight of the sintering composition. The content of metal of the metal complex in the sintering composition is at least 20 wt.% based on the total weight of the sintering composition.SELECTED DRAWING: Figure 1a
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to sintered compositions and methods for making same, uses of sintered compositions, sintered metal deposits and methods for forming same on substrates, methods of die attachment, methods for forming electrical circuits or interconnects on substrates, methods for forming joints, methods for producing sintered joints and soldered assemblies. [Background technology]

[0002] In the electronics industry, semiconductor device interconnection to a substrate is an important part of device packaging. In today's era of printed electronics, there is a great demand for interconnect materials with low temperature processing and high electrical and thermal conductivity.

[0003] Conductive adhesives and solder pastes, which are still widely used as interconnects, have limitations at high temperature operation that result in reliability problems such as solder joint fatigue and intermetallic growth. These materials also have relatively low thermal and electrical conductivity.

[0004] Sintered joints offer an alternative to soldered joints. For example, the formation of sintered joints using nanoparticles is beneficial because they can be sintered or fused at lower temperatures compared to the formation of soldered joints. Silver-based sintered materials are of great interest in printed electronics due to their higher thermal and electrical conductivity, especially when pure silver joints are formed. They also have less fatigue issues present in high temperature applications. Unlike soldering, the sintering phenomenon is an atomic diffusion process that eliminates the intermediate liquid phase of soldering, thus solving the problems of die chipping and swimming. Typically, metal die attach materials are based on technology platforms such as nanoparticle-based materials, micron-sized flakes in a polymer binder, or mixtures of metal micron flakes with metal-organic compounds. Nanoparticle-based die attach materials typically have separation issues due to the general tendency of nanoparticles to agglomerate, which, among other things, clogs the nozzles of inkjet printers and makes them generally difficult to handle. Apart from stability issues, these agglomerated nanoparticles are also a potential source of printing defects. Attempts have been made to address the aggregation problem by capping the nanoparticles with organic moieties that have long carbon chains. The interconnect materials along with the capped nanoparticles are usually composed of polymers, additives / activators, and organic solvents. These organic materials are one of the major concerns in the die attach industry because they worsen porosity and ultimately cause failures in thermal and power cycling.

[0005] A second approach, widely used by the industry for die attach applications, is to use a mixture of metal-organic compounds and metal flakes. The metal-organic compounds melt and decompose to form metallic bridges between the micron metal flakes, thereby increasing the metal contact points and coordination number, which in turn increases the densification of the metal layer, enhancing the strength of the material and the resulting assembly.

[0006] Another problem with prior art metal die attach materials is that such materials require many steps in their manufacture, increasing the time and cost of their manufacture. Thus, there is an incentive to provide metal sintering / die attach materials that require fewer steps in their manufacture in order to reduce the time and cost of their manufacture.

[0007] For example, WO 2014 / 068299 and WO 2015 / 155542 relate to sintered powders containing metal particles. The use of capping agents to prevent agglomeration is also discussed therein.

[0008] Literature reports describe the use of silver organic precursors such as silver neodecanoate and silver 2-ethylhexanoate, and copper precursors such as copper formate and copper acetate, for the synthesis of conductive inks for inkjet printing. The main drawback of metal-organic based conductive inks is their limited solubility in organic solvents, thereby dramatically reducing the possibility to increase the metal content of the composition. Low metal content limits the thickness of the lines that can be produced and also results in compositions with low viscosity that are undesirable for printing applications. Thus, there is an incentive to increase the metal content in compositions for use in sintering and / or die attach applications.

[0009] Many reported metal-organic inks are primarily used in flexible electronic applications such as radio frequency identification (RFID) readers, transponder antennas, interconnects for organic light emitting diodes (OLEDs), organic thin film transistors, and printed circuits on substrates. These metal-organic based molecular inks are not suitable for screen and stencil printing applications due to their extremely low viscosity. The viscosity of the die-attach material plays an important role in printing applications. Furthermore, the prior art inks have low metal content, and therefore the final result is a thin metal line or coating.

[0010] Therefore, there is a need to provide simpler, less expensive sintered compositions that are easier to manufacture, can provide improved bond strength, superior printed lines and circuits, and result in less carbon impurities in the joints, resulting in higher electrical and thermal conductivity. Summary of the Invention

[0011] The present invention seeks to address at least some of the problems associated with the prior art, or at least provide a commercially acceptable alternative thereto. Additionally, the present invention discloses the construction / fabrication of new assemblies, devices, and components using the disclosed materials and processes.

[0012] In a first aspect, the present invention provides a sintering composition consisting essentially of a solvent and a metal complex dissolved in the solvent, the sintering composition containing at least 60 wt. % of the metal complex, based on the total weight of the sintering composition, and the sintering composition containing at least 20 wt. % of the metal of the metal complex, based on the total weight of the sintering composition.

[0013] Additionally, the present invention provides examples of the use of this new composition in combination with the processes discussed herein to create new devices such as sintering die attach methods for power and other electronic devices, printed interconnects and circuits on various metal substrates and polymer substrates such as PET, PC, PI, etc., and coatings on various components, parts, and surfaces.

[0014] Each aspect or embodiment defined in this specification may be combined with any other aspect or embodiment unless expressly indicated otherwise. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature indicated as being preferred or advantageous.

[0015] As used herein, the term "sintered composition" can include compositions capable of forming sintered metal deposits or sintered joints. Without being bound by theory, it is believed that such sintering occurs as a result of atomic diffusion.

[0016] The term "metal complex" as used herein may include, for example, a metal cation complexed with a ligand, or a metal salt. A metal complex may include one or more different metal atoms of different elements. The metal center may be neutral or cationic. The ligand may be neutral or anionic.

[0017] The sintering composition consists essentially of a solvent and a metal complex dissolved in the solvent. The terms "consisting essentially of" or "consisting essentially of" as used herein should be interpreted as allowing for the presence of amounts of other components in addition to the essential components, as long as the essential characteristics of the claimed composition are not substantially affected by their presence. Thus, the term "consisting essentially of" as used herein also encompasses the occurrence of unavoidable impurities in the sintering composition that do not substantially affect the essential properties of the sintering composition. Preferably, the sintering composition consists of a solvent and a metal complex dissolved in the solvent. In an alternative preferred embodiment, the sintering composition comprises a solvent and a metal complex dissolved in the solvent.

[0018] By "consisting essentially of" or "consisting of" the recited elements, the sintered composition of the present invention is substantially free of metal particles. As used herein, the term "substantially" means that the sintered composition typically contains less than 1% by weight of metal particles, preferably less than 0.1% by weight of metal particles, based on the total weight of the sintered composition, and more preferably, the sintered composition is, for example, completely free of metal particles.

[0019] In addition, by "consisting essentially of" or "consisting of" the recited elements, the sintering composition is substantially free of metal complex particles. As used herein, the term "substantially" means that the sintering composition typically contains less than 1 wt. % of metal complex particles, preferably less than 0.1 wt. % of metal complex particles, based on the total weight of the sintering composition, and more preferably the sintering composition is completely free of metal complex particles. This may be possible due to the high solubility of the metal complex in the solvent. Since substantially all of the metal complex is dissolved in the solvent, the sintering composition may be substantially free of metal complex particles. In particular, at least 90% by weight of the metal complex in the sintering composition can be dissolved in the solvent, preferably at least 95% by weight of the metal complex in the sintering composition can be dissolved in the solvent, more preferably at least 98% by weight of the metal complex in the sintering composition can be dissolved in the solvent, even more preferably at least 99% by weight of the metal complex in the sintering composition can be dissolved in the solvent, based on the total amount of metal complex in the sintering composition, even more preferably at least 99.5% by weight of the metal complex in the sintering composition can be dissolved in the solvent, based on the total amount of metal complex in the sintering composition, even more preferably at least 99.9% by weight of the metal complex in the sintering composition can be dissolved in the solvent, most preferably the metal complex is completely dissolved in the solvent. Advantageously, since the sintering composition can be substantially free of particles of metal complexes and therefore substantially free of suspended particles, the sintering composition can have good long-term physical stability and also desirable properties for printing.

[0020] In addition, by "consisting essentially of" or "consisting of" the recited elements, the sintered composition is substantially free of organic polymers, preferably substantially free of polymers. As used herein, the term "substantially" means that the sintered composition typically comprises less than 1% by weight of organic polymer or polymers, preferably less than 0.1% by weight of organic polymer or polymers, based on the total weight of the sintered composition, and more preferably the sintered composition is completely free of organic polymer or polymers. Because the sintered composition of the present invention is substantially free of metal particles, no polymer or other additives or stabilizers are required to limit the agglomeration of any particles. Thus, the sintered composition is much simpler, contains fewer components, and is less complex. Advantageously, this can also mean that there may be fewer organic impurities in the sintered joints made using the sintered composition, allowing sintered joints to be made that are stronger and may exhibit improved thermal and electrical properties.

[0021] Additionally, by "consisting essentially of" or "consisting of" the recited elements, the sintered composition is substantially free of metal oxides. As used herein, the term "substantially" means that the sintered composition typically contains less than 1 wt. % of metal oxides, preferably less than 0.1 wt. % of metal oxides, based on the total weight of the sintered composition, and more preferably the sintered composition is completely free of metal oxides.

[0022] The sintering composition contains at least 60 wt. % of the metal complex, based on the total weight of the sintering composition. Accordingly, the metal content in the sintering composition can be maximized / optimized. A large amount of complex in the composition, i.e. a large complex-to-solvent ratio, can provide a composition with sufficient and desirable viscosity for printing applications. In addition, a correspondingly smaller amount of solvent can allow the solvent to be completely removed as a result of a lower temperature (pre-sintering) drying step and / or a shorter (pre-sintering) drying step. Preferably, the sintering composition contains at least 70 wt. %, more preferably at least 75 wt. %, based on the total weight of the sintering composition. The ability to provide at least 60 wt. % of the metal complex in solution (as opposed to a suspension) is a result of the unique method of making the sintering composition described below. The sintering composition can contain up to 95 wt. % of the metal complex, for example up to 90 wt. % of the metal complex or up to 85 wt. % of the metal complex. The sintering composition preferably contains up to 95 wt. % of the metal complex, more preferably up to 90 wt. % of the metal complex, even more preferably up to 85 wt. % of the metal complex.

[0023] The sintering composition essentially consists (or consists of) a solvent and a metal complex dissolved in the solvent. Accordingly, the sintering composition may contain, for example, 5-40 wt. % of the solvent, or 10-35 wt. % of the solvent, or 15-30 wt. % of the solvent, or 15-25 wt. % of the solvent, based on the total weight of the sintering composition.

[0024] The sintering composition contains at least 20% by weight of metal of the metal complex based on the total weight of the sintering composition. In other words, the total amount of metal in the sintering composition is at least 20% by weight, all of which is in the form of metal complex dissolved in a solvent. A high concentration of metal in the sintering composition means that less solvent must be evaporated during the pre-sintering drying step. Advantageously, this can reduce the time and cost of the sintering process. Furthermore, a higher concentration of metal in the sintering composition means that the sintering composition can be more viscous, which is desirable for printing applications. Increasing the metal content also promotes densification of the sintered layer, thereby increasing the bond line thickness of the joints in the assembly, which can result in greater bond strength. This can also allow thicker lines to be produced without the need to perform multiple deposition and sintering steps. Preferably, the sintering composition contains at least 25% by weight of metal based on the total weight of the sintering composition, preferably at least 30% by weight of metal based on the total weight of the sintering composition, more preferably at least 35% by weight of metal, even more preferably at least 40% by weight of metal, even more preferably at least 50% by weight of metal based on the total weight of the sintering composition. The sintering composition may contain up to 95% by weight of metal, for example up to 90% by weight of metal, or up to 85% by weight of metal. In a preferred embodiment, the sintering composition contains 60-80% by weight of metal, based on the total weight of the sintering composition.

[0025] The inventors have surprisingly found that the sintering compositions described herein can be used as an improved replacement for nanoparticle-based materials, micron-sized flakes in polymer binders, and / or mixtures of metal micron flakes with metal-organic compounds for die-attach applications. Surprisingly, it has been found that the sintering compositions can be sintered at low temperatures and / or pressures to provide joints that still exhibit high die shear strength and / or high peel strength compared to those of the prior art and that may have low organic impurities. This may be due to the absence of other components in the composition, such as rheology modifiers and polymers, which allows, for example, the production of purer sintered metal deposits or sintered joints.

[0026] Furthermore, the sintered compositions described herein can be produced more simply, i.e., with fewer steps and using fewer starting materials, resulting in less complexity, compared to prior art sintered compositions / powders. In particular, the production of the sintered compositions can be a single-step process. Advantageously, the preparation of the sintered compositions does not require the intermediate step of producing (metal) powders. This has the advantage that the sintered compositions of the present invention can be produced at lower cost while achieving comparable, or indeed improved, sintering properties. Sintered joints produced using the sintered compositions described herein can advantageously exhibit less organic impurities than those produced using prior art sintered powders, due to the simpler composition, consisting essentially of a solvent and a metal complex dissolved in the solvent. The sintered compositions of the present invention eliminate the use of any polymers, binders, activators, or additives. This, in turn, is believed to contribute to the superior bond strength and reliability that can be exhibited by the sintered metal deposits and / or sintered joints described herein.

[0027] Advantageously, the sintered compositions described herein are typically chemically and physically stable at room temperature. In practice, this may allow the sintered compositions to be stored at room temperature for extended periods of time before use, reducing storage costs. For example, when kept in amber bottles and refrigerated conditions, the sintered compositions typically do not exhibit changes in viscosity and their performance does not deteriorate over time.

[0028] Sintered metal deposits and / or sintered joints formed using the sintering compositions described herein may also exhibit high thermal and electrical conductivity at processing temperatures and pressures much lower than those of conventional sintering compositions. These advantageous properties may result, for example, from the high purity and densified metal deposits and metal joints that may be formed.

[0029] The sintered compositions described herein may also be described as "metal gels." These terms may be used interchangeably herein.

[0030] The formation of the sintering composition depends on the solubility of the metal complex in the solvent, preferably an organic solvent. Typically, the metal complex has a high solubility in the solvent.

[0031] Due to the typically high solubility of metal complexes, the sintering compositions described herein do not require any organic polymers or stabilizers in the formulation. Without wishing to be bound by theory, it is believed that the decomposition of metal complexes by drying and heating leads to the formation of smaller (metal) particles that diffuse to the interface between the substrate and the die under pressure sintering, resulting in robust bond strength. Thus, the low cost, high-end performance, long shelf life, and high electrical and thermal attributes of the sintering compositions may provide surprising advantages over existing die attach materials.

[0032] Unlike prior art conductive inks, the sintered composition described herein can be used in a variety of die attach applications due to its typically high metal content and high viscosity, making it a more versatile material compared to other sintered materials or conductive inks.

[0033] For example, the sintered composition of the present invention may enable the fabrication of circuits on flexible substrates such as PET and PI. This may therefore enable a futuristic approach for next-generation electronics assembly. Fabricating circuits on flexible substrates can be easily produced using the metal gel / sintered composition disclosed herein under suitable process conditions, thereby opening up the scope of, for example, mounting solder components on flexible substrates. Also, due to the advantages described herein, the current carrying capacity of interconnect lines and circuits fabricated using metal gel is far superior to any other existing sintered / soldered materials that apply gel / composition to the edge on the soldering material.

[0034] Without wishing to be bound by theory, it is understood that upon heating, the metal complexes of the sintering composition will precipitate out of solution, melt, and decompose. Organics in the sintering composition, which may include solvents and / or ligands of the metal complexes, may then evaporate during a drying step prior to sintering, resulting in substantially no carbon residue in the joint after sintering. Because the sintering composition is substantially free of metal particles or particles of metal complexes, the presence of rheology modifiers, stabilizers, or polymers is not necessary for the stability of the sintering composition. This means that it is possible to create printable die attach materials that are carbon-free.

[0035] To date, reported die attach materials contain some amount of organic materials for stability. These organic materials are believed to be the main contributors to thermal and electrical fatigue. The joints made with the sintered compositions described herein are typically carbon-free. Thus, the electrical, thermal, and mechanical properties of the joints are typically superior compared to other reported die attach materials.

[0036] In addition, the sintering composition / metal gel described herein may have unique soldering characteristics on its surface. The gel may be easily soldered. The gel may be printed on a metal or polymer flexible substrate to which the solder component may be attached by soldering. This advantageously allows, for example, components to be attached to non-metallic substrates, such as polymer flexible substrates. It is not usually possible to successfully apply solder to deposits made using conventional sintering compositions. This is because such conventional sintering compositions typically contain species, such as polymers, that may remain in the sintered joint or cause voids in the sintered joint, which may interfere with soldering.

[0037] In addition, the sintering compositions / metal gels described herein can be advantageously used on flexible substrates. The resulting sintered material is densified compared to sintered materials formed using conventional sintering materials. This is due to the higher metal content of the sintering compositions described herein. Such higher density allows for printing of features (circuit lines, interconnects, joints, etc.) that are thin enough to ensure flexibility while also exhibiting sufficient electrical conductivity. Features formed using conventional sintering compositions with lower metal content exhibit insufficient conductivity when made thin enough to provide flexibility, and vice versa.

[0038] Typically, the metal complex substantially decomposes over a temperature range below 20°C, preferably below 15°C, more preferably below 10°C. This means, for example, that if the metal complex begins to decompose at a temperature of X°C upon heating, then the metal complex is preferably substantially decomposed at a temperature of X+20°C, preferably at least 95% by weight, more preferably at least 99% by weight, based on the total weight of the metal complex in the sintering composition, or most preferably, all of the metal complex decomposes. This is advantageous, at least because it may allow the metal complex to decompose into pure metal without initiating sintering during the drying step described herein. Thus, the subsequent sintering step may be carried out in the presence of only very small amounts, or in the total absence, of any metal complex or ligand. This may therefore result in, for example, a purer joint.

[0039] Typically, the metal complex is highly concentrated in the solvent. Preferably, the solvent is supersaturated with the metal complex. This supersaturation may be made possible by the high solubility of the metal complex in the solvent. Advantageously, this supersaturation may make it possible to maximize / optimize the metal content of the sintering composition. The term "supersaturated" as used herein encompasses the situation where the concentration of the metal complex in the solvent exceeds the concentration of the saturation point, i.e., the solution contains more dissolved metal complex than can be dissolved by the solvent under normal circumstances. Furthermore, supersaturated solutions are more viscous. Sintering compositions with high viscosity are generally preferred for printing applications.

[0040] Typically, the metal complex substantially decomposes during application of the sintering composition, for example during the manufacture of a sintered metal deposit or sintered joint, at a temperature lower than the sintering temperature used. Preferably, the metal complex substantially decomposes during the drying step described herein at a temperature that allows substantially all of the metal complex to decompose. In particular, the metal complex preferably substantially decomposes at a temperature below 200°C, more preferably below 190°C. In some embodiments, the metal complex may substantially decompose at a temperature below 180°C, or below 170°C, or below 160°C. The term "decomposition" as used herein encompasses the breakdown of a single entity into two or more fragments / components. Typically, the term "decomposition" as used herein encompasses the breakdown of a metal complex into the metal, which may be individual atoms or small particles / clusters of the metal, as well as the ligands and / or organic components of the metal complex. As used herein, the term "substantially" typically means that at least 90% by weight, preferably at least 95% by weight, more preferably at least 99% by weight of the metal complex decomposes based on the total weight of the metal complex, or most preferably means that all of the metal complex decomposes. Advantageously, the metal complex may substantially decompose at low temperatures. This means that substantially all of the metal complex may decompose at low temperatures, and then substantially all of the solvent and substantially all of the ligands of the metal complex may evaporate during a low-temperature drying step. Thus, the low sintering temperatures applied in the methods described herein may reduce impurities, organics, or other potential in the resulting sintered joint, and thus improve the strength and / or thermal and electrical properties of the sintered joint. Without wishing to be bound by theory, it is believed that when the metal complex decomposes, the ligands / components other than the metal may evaporate, leaving the metal to be sintered in a subsequent sintering step to form the sintered joint.

[0041] Typically, the solvent and / or the ligand of the metal complex have a boiling point that allows them to evaporate during a pre-sintering drying step, such as the drying step of the method described herein. Preferably, the solvent and / or the ligand of the metal complex have a boiling point that allows substantially all of the solvent and / or the ligand of the metal complex to evaporate during the drying step described herein. In particular, the solvent and / or the ligand of the metal complex typically have a boiling point below 300° C., preferably below 250° C., more preferably below 200° C. Advantageously, this means that at the low temperatures applied in the drying step, substantially all of the solvent and / or the ligand of the metal complex can evaporate, leaving the metal to be sintered to form the sintered joint. Thus, at the low sintering temperatures applied in the method described herein, the possibility of impurities, organics or other in the resulting sintered joint can be reduced, and therefore the strength and / or thermal and electrical properties of the sintered joint can be improved. As used herein, the term "substantially" typically means that at least 90% by weight, preferably at least 95% by weight, more preferably at least 99% by weight of the solvent and / or ligand of the metal complex is evaporated, based on the total weight of the solvent and / or ligand of the metal complex, or most preferably, all of the solvent and / or ligand of the metal complex is evaporated. The length of the drying step described herein typically allows for sufficient solvent and / or ligand of the metal complex to evaporate, for example, without boiling the solvent. High temperatures during the drying step are undesirable, as they would allow the solution to agitate and form, contact, and possibly sinter, metal nanoparticles.

[0042] The metal of the metal complex is preferably selected from one or more of silver, gold, platinum, palladium, nickel, copper, and molybdenum. Most preferably, the metal of the metal complex is copper and / or silver. Copper and silver are desirable metals for forming sintered joints because they exhibit good properties for sintered joints, in particular good thermal and electrical conductivity.

[0043] Typically, the solvent of the sintering composition comprises an organic solvent, preferably the solvent is an organic solvent. Preferably, the solvent is selected such that the metal complex is highly soluble in the solvent and / or the solvent has a boiling point as described above. The solvent is preferably an alcohol, for example a monohydric, dihydric or trihydric alcohol. Preferably, the solvent is selected from one or more of propane-1-2-diol, terpineol, triethylene glycol, glycerol and 2-methyl-1,3-propanediol, more preferably terpineol or glycerol.

[0044] The metal complex may include a metal-organic complex. For example, preferably the metal complex is a metal carboxylate, and preferably the carboxylate has the structure RCOO - and R is a branched or unbranched hydrocarbon chain having 14 or less carbon atoms, preferably 12 or less carbon atoms, more preferably 10 or less carbon atoms. R may also be a hydrocarbon chain having 2 or less carbon atoms. R may be a hydrogen atom, preferably a branched or unbranched hydrocarbon chain having 1 or more carbon atoms, more preferably 2 or more carbon atoms. For example, R may be a branched or unbranched hydrocarbon chain having 6 to 14 carbon atoms, preferably 8 to 12 carbon atoms. This is preferred, for example, when the metal of the metal complex is silver. Alternatively, R may be a hydrogen atom, or a branched or unbranched hydrocarbon chain having 1 to 4 carbon atoms, preferably a hydrogen atom, or a hydrocarbon chain having 1 or 2 carbon atoms. This is preferred, for example, when the metal of the metal complex is copper. Preferred ligands include neodecanoic acid, 2-ethylhexanoate, formic acid, and acetate.

[0045] For example, preferably, the metal complex is selected from one or more of silver neodecanoate, silver 2-ethylhexanoate, silver oxalate, silver lactate, silver hexafluoroacetylacetonate cyclooctadiene, copper formate tetrahydrate, and copper acetate, preferably silver neodecanoate or copper formate tetrahydrate. For example, silver neodecanoate contains about 38% by weight of silver. Thus, since the metal complex may be saturated or supersaturated in the sintering composition, it may be possible to provide a sintering composition with a metal / silver content of about 28% by weight or more by dissolving silver neodecanoate or another metal complex disclosed herein at high temperature. Typically, when the metal of the metal complex is copper, the copper content of the sintering composition may be about 22.5% by weight or more.

[0046] The viscosity of the sintering composition may be 60,000 to 120,000 cP, preferably 70,000 to 80,000 cP. Such a viscosity may result from the large amount of metal complexes contained in the sintering composition. The viscosity of the sintering composition may make it suitable for screen and stencil printing, thereby making it desirable for use in the die attach industry. The viscosity may be measured with a Brookfield viscometer (HB DV-III) spindle CP51. The viscosity is measured, for example, at a temperature of 25° C., a shear rate of 3.84 / sec, and 1 RPM.

[0047] Preferably, the sintered composition is in the form of a gel, more preferably in the form of a metal gel. As used herein, the term "gel" refers to a sol in which the particles are meshed to result in a rigid or semi-rigid mixture. Sintered compositions are typically for die attach applications.

[0048] Preferably, the sintered composition of the invention is in the form of a gel, preferably a metal gel, or a free-standing film or foil, or coated, deposited, printed or laminated onto a wafer, or coated, deposited, printed or laminated onto a substrate made of glass and / or ceramic and / or metal and / or polymeric film and / or composite material used as a printed circuit board. Such a form of the sintered composition may make it more useful in different die attach applications.

[0049] In a further aspect, the present invention provides a method for producing a sintered composition as described herein, the method comprising providing a solvent, providing a metal complex, and dissolving the metal complex in the solvent at a temperature between 100° C. and 180° C. to form a solution.

[0050] The advantages and preferred features of the first aspect apply equally to this aspect.

[0051] Dissolving the metal complex at such high temperatures allows more of the metal complex to be dissolved in the sintering composition, for example at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight. As discussed above, such high metal complexes can provide a sintering composition with an advantageously high viscosity compared to conventional sintering compositions. Typically, the mixture of metal complex and solvent is stirred to facilitate dissolution.

[0052] Preferably, the solution is supersaturated. Preferably, the method further comprises cooling the solution to a temperature of 30-60° C., preferably to a temperature of 40-50° C. Without wishing to be bound by theory, it is believed that this process of heating and cooling may allow for the formation of a supersaturated solution, preferably a stable supersaturated solution.

[0053] Preferably, the method further comprises milling the solution, typically once cooled in the manner described above. Typically, milling results in a homogenous metal gel. Without wishing to be bound by theory, it is believed that the milling step may reduce the likelihood of precipitation of metal complexes from the solution, especially once cooled. Preferably, milling is carried out in a three-roll mill, although other milling methods may be used. The solution may also be homogenized in an orbital mixer, for example at 500-1500 RPM, such as 1000 RPM, for example for 1-20 minutes, such as 10 minutes.

[0054] Preferably, dissolving the metal complex in the solvent is carried out at a temperature between 110°C and 150°C, more preferably between 120°C and 140°C, even more preferably at a temperature of about 130°C.

[0055] Preferably, the sintered composition does not contain any metal particles and / or does not contain any particles of metal complexes, which may allow the sintered composition to have high chemical and physical stability, as well as properties desirable for printing applications, as described above.

[0056] In a further aspect, the present invention provides a method of forming a sintered metal deposit on a substrate, the method comprising providing a substrate, disposing a sintering composition as described herein on the substrate, drying the composition at a temperature between 140°C and 200°C to form a dry composition, and sintering the dry composition at a temperature between 150°C and 300°C, wherein the sintering is carried out at a temperature higher than the temperature of drying.

[0057] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0058] Typically, the drying step serves to remove substantially all of the solvent and other organic substituents of the metal complex, such as the ligands of the metal complex, leaving behind a deposit that is substantially metallic, i.e., a deposit that essentially consists of the metal of the metal complex. For example, the dried deposit may contain 95% or more by weight of metal, typically 98% or more by weight of metal, the remainder typically being composed mainly of graphitized carbon. The resulting metal deposit may then be sintered to form a substantially pure sintered metal deposit. Sintering is carried out at a temperature higher than the temperature of drying, whereby the metal is preferably not sintered until the drying step is completed. As will be understood by those skilled in the art, the relative temperatures of the drying and sintering steps will vary depending on the identity of the metal, solvent, and metal complex of the sintered composition.

[0059] Preferably, the substrate is a flexible substrate, preferably comprising one or more of polyethylene terephthalate (PET), polycarbonate (PC), polyimide (PI), thermoplastic polyurethane (TPU), polyethylene naphthalate (PEN) and polyether ether ketone (PEEK). Advantageously, the sintering composition of the invention allows a sufficiently low sintering temperature to be applied so that damage and / or warping to such substrates can be limited or even avoided. In addition, as discussed above, the sintering composition is flexible and capable of forming sintered deposits that exhibit sufficient electrical conductivity.

[0060] Alternatively, the substrate may be a rigid substrate, preferably comprising FR4, glass, a ceramic such as Al2O3, SiC, or SiO2, a semiconductor material such as Si, SiC, Ge, or GaN, or a metal foil such as a metal foil formed of Cu, Ag, Au, Al, Ni, or an alloy.

[0061] Preferably, disposing the sintering composition on the substrate comprises stencil printing and / or screen printing the sintering composition onto the substrate. As described herein, the sintering composition of the present invention has desirable properties for printing, such as suitable viscosity and being substantially free of any metal particles or particles of metal complexes.

[0062] Preferably, the metal complex of the sintering composition comprises silver and drying is carried out at a temperature of 170°C to 190°C for 30 to 90 minutes, or the metal complex of the sintering composition comprises copper and drying is carried out at a temperature of 150°C to 170°C for 15 to 60 minutes under a nitrogen atmosphere. Preferably, the drying step has suitable temperature and time conditions to allow the metal complex to substantially decompose and the solvent and / or ligands of the metal complex to substantially evaporate by the end of the drying step, but without substantial sintering of the metal particles. As will be appreciated, higher drying temperatures may require shorter drying times and vice versa. The use of a nitrogen atmosphere may limit, and preferably prevent, oxidation of the metal, especially when the metal is copper.

[0063] Sintering is carried out at a temperature between 150°C and 300°C. Preferably, sintering is carried out at a temperature between 180°C and 295°C, preferably between 200°C and 290°C, more preferably between 210°C and 285°C, even more preferably between 240°C and 280°C, even more preferably between 250°C and 270°C. Such low sintering temperatures have many advantages, including a reduced risk of damage to the substrate, in addition to desirable economic benefits. Thus, the process may be simpler and less specialized equipment may be required. Temperatures below 150°C may result in insufficient and / or slow sintering.

[0064] Typically, the sintering step is performed at a pressure of 2 MPa to 15 MPa, preferably 4 MPa to 12 MPa. In addition to the sintering temperature, such sintering pressures may, for example, allow a strong metal deposit with low porosity to be formed, thereby allowing the metal to sinter effectively to form a sintered joint that may have high die shear strength and high peel strength. Typically, heat and pressure are applied simultaneously. Typically, pressure is applied using a Carver press, such as a Carver 3891CEB.4NE1001. Advantageously, the sintered compositions described herein may be able to provide strong sintered joints with fewer impurities at these low sintering pressures. Such low sintering pressures are desirable in the industry, among other things, to save costs and reduce potential damage to the substrate and / or die.

[0065] The sintered metal deposit may include a bond between the die and the substrate, thereby connecting the die and the substrate.

[0066] Alternatively, the sintered metal deposit may include an electrical circuit or interconnect, for example, the sintered metal deposit may be an electrical circuit or interconnect.

[0067] The sintered deposit may also include a coating, for example the sintered deposit may be a coating.

[0068] Preferably, the sintered metal deposit is substantially free of metal complexes and / or substantially free of organic ligands and / or substantially free of organic materials and / or substantially free of carbon. As used herein, the term "substantially" means that the joint typically contains no more than 2% by weight of metal complexes and / or organic ligands and / or organic materials and / or carbon, and preferably less than 1% by weight of metal complexes and / or organic ligands and / or organic materials and / or carbon, more preferably less than 0.1% by weight of metal complexes and / or organic ligands and / or organic materials and / or carbon, based on the total weight of the joint. More preferably, the joint is completely free of metal complexes and / or organic ligands and / or organic materials and / or carbon. Such joints, lacking impurities, can be stronger, i.e., have high die shear strength and high peel strength, while at the same time exhibiting good thermal and electrical conductivity properties.

[0069] Preferably, the sintered metal deposit has a die shear strength of 30 MPa or more, preferably 40 MPa or more, more preferably 50 MPa or more. Typically, the die shear strength is measured using a Dage4000PXY. The shear strength is typically measured using a shear rate of 700 microns / sec and a shear height of 0 microns.

[0070] Typically, after 1000 cycles of thermal shock testing from +150°C to -50°C with a dwell time of 3 minutes, the porosity in the sintered metal deposit is 0.5% or less, preferably 0.3% or less, and / or after 3000 cycles of thermal shock testing from +150°C to -50°C with a dwell time of 3 minutes, the porosity in the sintered metal deposit is 1.5% or less, preferably 1.0% or less. As used herein, the term "thermal shock testing" encompasses testing that evaluates damage caused by sudden temperature fluctuations that cause stresses in an object. Porosity is, for example, the volume or area fraction, typically the area fraction, that is not occupied by material in the sintered joint, i.e., caused by holes and / or voids. It can be estimated from an X-ray image of the sintered joint. Porosity can be measured by X-ray analysis, typically using a Phoenix X-ray (Microme / X-180).

[0071] Preferably, the peel strength of the sintered metal deposit is 10 N / mm or more, preferably 15 N / mm or more, more preferably 20 N / mm or more. Typically, the peel strength is measured using an Imada peel tester, preferably model MX2-110.

[0072] Preferably, the sintered metal deposit is solderable and / or capable of high current carrying. High current density carrying capability is defined in relative terms. In this case, high current density carrying capability is the ability to carry a higher current density than other inks, such as conventional screen printable conductive inks containing Ag particles or Ag flakes. Such inks printed on insulating substrates can carry current densities of up to 10 A / mm 2 Maximum current densities on the order of 10 A / mm can be sustained. Even under these low current conditions, adverse heating and subsequent failure is possible. However, the metal gel / sintered composition of the present invention can sustain current densities 2-10 times higher than flake inks, e.g., 10 A / mm 2 or more than 15A / mm 2 or more than 20A / mm 2 or more than 50A / mm 2 or more, or up to 100A / mm 2Although these numbers vary depending on the substrate and ambient conditions, these relatively particle-free gels can sustain much higher current densities than conventional inks filled with Ag or other conductive particles.

[0073] Preferably, the sintered metal deposit is flexible, which may allow the use of the sintered metal deposit on flexible substrates such as, for example, PET and PI, providing a diverse range of applications for the sintered metal deposit.

[0074] Preferably, the sintered metal deposit (typically a silver deposit) exhibits a sheet resistance of less than 12 mΩ / sq / mil. Such sintered metal deposits therefore have excellent electrical conductivity and are desirable for use in many applications in the electronics industry. Electrical conductivity, resistivity, and sheet resistance can be measured using a four-point probe method. In this method, all electrical conductivity measurements can be performed with an Agilent 34411A multimeter. Wires soldered to the pads are connected to the Agilent 34411A multimeter to measure resistance. The resistance values ​​and dimensions of the printed lines are used to determine the bulk resistivity (ρ), sheet resistance (R s ) and electrical conductivity (σ) are obtained using the formulas given below: Bulk resistivity, ρ=R×A / l, Sheet resistance, R s = R × W / l R = resistance of printed and sintered metal gel A = width (W) x thickness (t) (of the printed cured line) l = length of printed cure line W = width of printed cure line Electrical conductivity (σ) = 1 / ρ

[0075] In a further aspect, the present invention provides a sintered metal deposit formed using the sintering composition described herein, preferably the sintered metal deposit is formed using the method described herein.

[0076] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0077] Preferably, the sintered metal deposit comprises a bond between a die and a substrate, an electrical circuit or interconnect, or a coating.

[0078] In a further aspect, the present invention provides a method of die attachment comprising providing a substrate and a die; disposing a sintered composition as described herein between the substrate and the die; drying the composition at a temperature of 140-200°C to form a dry composition; and sintering the dry composition at a temperature of greater than 150°C to 300°C and a pressure of 2 MPa to 15 MPa to attach the die to the substrate, wherein the sintering is performed at a temperature higher than the temperature of drying.

[0079] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0080] The sintering composition is typically in contact with both the substrate and the die. Drying can occur while the sintering composition is between the substrate and the die. Alternatively, the sintering composition can be applied to one of the substrate or the die and then dried before contacting the other of the substrate or the die. In other words, drying can be performed when the sintering composition is in contact with both the substrate and the die, or when the sintering composition is in contact with only one of the substrate and the die.

[0081] Typically, the drying step serves to remove substantially all of the solvent and other organic substituents of the metal complex, such as ligands of the metal complex, leaving behind a substantially metal deposit between the substrate and the die, i.e., a deposit consisting essentially of the metal of the metal complex. The resulting metal deposit between the substrate and the die can then be sintered to form a substantially pure sintered metal deposit. Sintering is carried out at a temperature higher than the temperature of drying, so that the metal is preferably not sintered until the drying step is completed. As will be appreciated by those skilled in the art, the relative temperatures of the drying and sintering steps will vary depending on the identity of the metal, solvent, and metal complex of the sintering composition.

[0082] Sintering is carried out at a pressure between 2 MPa and 15 MPa. Preferably, sintering is carried out at a pressure between 4 MPa and 12 MPa. In addition to the sintering temperature, such sintering pressures can, for example, allow a strong metal deposit having low porosity to be formed, thereby providing a strong substrate-die bond.

[0083] In a further aspect, the present invention provides a method of forming an electrical circuit or interconnect on a substrate, the method comprising: The method includes providing a substrate, disposing a sintered composition described herein on the substrate in the form of a circuit or interconnect, drying the composition at a temperature of 140-200°C to form a dry composition, and sintering the dry composition at a temperature of 150°C to 300°C to form the circuit or interconnect, wherein the sintering is performed at a temperature higher than the temperature of drying.

[0084] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0085] The sintered composition, arranged in the form of a circuit or interconnect, can be sintered to form a substantially pure sintered metal deposit. Sintering is carried out at a temperature higher than that of drying, so that the metal is preferably not sintered until the drying step is completed. This ensures that sintering occurs only in the substantial absence of organic materials, thereby reducing impurity and void formation in the final circuit or interconnect. As will be appreciated by those skilled in the art, the relative temperatures of the drying and sintering steps will vary depending on the identity of the metal, solvent, and metal complex of the sintered composition.

[0086] The advantages of the above-described methods of die attachment or methods of forming electrical circuits or interconnections on a substrate are comparable to those of the above-described methods of forming sintered metal deposits on a substrate.

[0087] In a further aspect, the present invention provides a method of manufacturing a soldered assembly, the method including forming a sintered metal deposit on a substrate according to the methods described herein, depositing a solder paste on the sintered metal, contacting a component with the deposited solder paste, and reflowing the solder paste to provide a soldered assembly.

[0088] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0089] Typically, the solder paste deposited on the sintered metal is wet, that is, molten and contains flux.

[0090] As used herein, the term "substrate" may include metal substrates, such as copper, direct bond copper (DBC), direct plate copper (DPC), metal core printed circuit board (MCPCB), FR4, copper lead frame, flexible PCB, gold, silver, aluminum, steel, and substrates with various surface finishes, such as organic solderability preservative (OSP) and electroless nickel immersion gold (ENIG). Alternatively, other substrates, such as non-metallic substrates, may be used, such as glass, polymeric films, silicone, ceramic, and plastics, such as polyimide (PI) or polyethylene terephthalate (PET). In this method, preferably PI, PET, or FR4 substrates are used.

[0091] Typically, the solder paste is a tin / bismuth solder paste, although other solder pastes may be used. For example, the solder may include one or more of SAC solder, ULTS solder, high lead solder, AuSn solder, and Zn-based solder.

[0092] The soldered assembly may have high temperature applications for wire harnesses in automotive applications.

[0093] Advantageously, the metal gels disclosed herein can exhibit good wetting properties of the solder on the metal gel printed on the substrate.

[0094] Typically, the substrate and sintering composition are pre-dried under nitrogen. Preferably, the solder paste is reflowed under nitrogen or air.

[0095] Preferably, the component is selected from an electronic component, an LED, and a metallized printed circuit board. Preferably, the substrate is selected from a carrier film, an interposer, or a circuit board.

[0096] In a further aspect, the present invention provides the use of the sintered composition as described above in a method selected from die attachment, wafer-to-wafer bonding, hermetic and near-hermetic sealing, dispensing, and producing circuitry or interconnect lines.

[0097] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0098] The sintered compositions described herein can be particularly effective in these applications due to the advantageous properties of the sintered compositions described herein and the resulting sintered metal deposits.

[0099] In a further aspect, the present invention provides the use of the sintered composition described herein in any of the methods described herein to produce an electric / electronic device, interconnect, assembly, circuit, or printed cable and wire harness.

[0100] The advantages and preferred features of the other aspects of the invention apply equally to this aspect.

[0101] Preferably, the assembly and / or circuit is a flexible or thermoformed and / or injection molded 3D electronic structure. Preferably, the assembly and / or circuit is solderable and capable of carrying high current densities. [Brief description of the drawings]

[0102] The invention will now be discussed in relation to the following non-limiting figures. [Figure 1a] FIG. 1 shows a FESEM cross-section of a joint made using a metal gel according to the present invention. [Figure 1b] FIG. 1 shows a FESEM cross-section of a joint made using a metal gel according to the present invention. [Figure 2a] 13 shows a microscope image of the failure mode of the substrate side of an assembled sample according to an embodiment of the present invention. [Figure 2b] 13 shows a microscope image of the ribbon-side failure mode of an assembled sample according to an embodiment of the present invention. [Figure 3a] 13 shows a FESEM micrograph of the failure mode on the substrate side of an assembled sample according to an embodiment of the present invention. [Figure 3b] 13 shows FESEM micrographs of ribbon-side failure modes of assembled samples according to embodiments of the present invention. [Figure 4a] 13 shows an X-ray analysis of the porosity of an assembled sample according to an embodiment of the present invention after being subjected to 0 cycles of thermal shock testing. [Figure 4b] 13 shows an X-ray analysis of the porosity of an assembled sample according to an embodiment of the present invention after being subjected to 1000 cycles of thermal shock testing. [Figure 4c] 13 shows an X-ray analysis of the porosity of an assembled sample according to an embodiment of the present invention after being subjected to 3000 cycles of thermal shock testing. [Figure 5a] FIG. 13 shows a FESEM cross-section of an assembled sample according to an embodiment of the present invention after being subjected to 3000 cycles of thermal shock testing. [Figure 5b]FIG. 13 shows a FESEM cross-section of an assembled sample according to an embodiment of the present invention after being subjected to 3000 cycles of thermal shock testing. [Figure 5c] FIG. 13 shows a FESEM cross-section of an assembled sample according to an embodiment of the present invention after being subjected to 3000 cycles of thermal shock testing. [Figure 6a] 13 illustrates the peel strength failure mode of the DBC side of an assembled specimen according to an embodiment of the present invention. [Figure 6b] 13 illustrates the ribbon-side peel strength failure mode of assembled samples according to an embodiment of the present invention. [Figure 7a] FIG. 1 shows an SEM cross-section of solder on metal gel on FR4 substrate according to an embodiment of the present invention. [Figure 7b] FIG. 1 shows an SEM cross-section of solder on metal gel on FR4 substrate according to an embodiment of the present invention. [Figure 7c] FIG. 1 shows an SEM cross-section of solder on metal gel on FR4 substrate according to an embodiment of the present invention. [Figure 8a] FIG. 1 shows a FESEM cross-section of an assembled sample according to an embodiment of the present invention. [Figure 8b] FIG. 13 shows a FESEM cross-section of the die interface of an assembled sample according to an embodiment of the present invention. [Figure 8c] FIG. 13 shows a FESEM cross-section of the die interface of an assembled sample according to an embodiment of the present invention. [Figure 8d] FIG. 13 shows a FESEM cross-section of the substrate interface of an assembled sample according to an embodiment of the present invention. [Figure 8e] FIG. 13 shows a FESEM cross-section of the substrate interface of an assembled sample according to an embodiment of the present invention. [Figure 9a] 1 shows an image of SnBi solder paste printed and reflowed under nitrogen / air on the printed surface of a metal gel according to the present invention printed on a FR4 / PI substrate. [Figure 9b] 1 shows an image of SnBi solder paste printed and reflowed under nitrogen / air on the printed surface of a metal gel according to the present invention printed on a FR4 / PI substrate. [Figure 9c] 1 shows an image of SnBi solder paste printed and reflowed under nitrogen / air on the printed surface of a metal gel according to the present invention printed on a FR4 / PI substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0103] The invention will now be discussed with reference to the following non-limiting examples.

[0104] Materials and equipment: material: Silver neodecanoate, 95%, was purchased from GelestINC. Propane-1,2-diol, tri-ethylene glycol, and 2-methyl 1,3 propanediol were purchased from SDFCL. Terpineol (mixture of isomers) was purchased from Loba chemie. Copper(II) formate tetrahydrate was purchased from Alfa Aesar. 3-(Dimethylamino)-1,2-propanediol was purchased from Tokyo Chemical Industry. Glycerol (98%) was purchased from Merck. 1-Ethyl-2-pyrrolidinone was purchased from Advent.

[0105] All of the above materials were analytical grade reagents and were used without further purification.

[0106] Device: Die shear was performed on a Dage 4000PXY. Die attachment was done with a Carver (3891CEB.4NE1001). The viscosity was measured with a Brookfield viscometer (HB DV-lll) Spindle CP51. X-ray analysis was performed with a Phoenix X-ray (Microme / X-180). Peel strength was measured using an IMADA peel tester (model MX2-110).

[0107] experiment: (1) Synthesis of silver metal gel: Example 1-I: 12 g of silver neodecanoate was weighed into a two-neck round bottom flask equipped with a thermometer and a condenser. To the silver precursor, 4.05 g of terpineol and 0.45 g of propane-1-2-diol were added. The reaction mixture was then heated at 85° C. with constant stirring until all the silver neodecanoate was completely dissolved. The resulting mixture was then allowed to cool and then crushed to obtain a homogenous metal gel. Since the silver compound is highly photosensitive, the particle-free metal gel was kept in an opaque or amber bottle under refrigerated conditions. The results are shown in Table 1.

[0108] [Table 1]

[0109] Example 1-II: 12 g of silver neodecanoate was weighed into a two-neck round bottom flask equipped with a thermometer and a condenser. To the silver precursor, 4 g of terpineol was added. The reaction mixture was then heated at 85° C. with constant stirring until all the silver neodecanoate was completely dissolved. The resulting mixture was then allowed to cool and then crushed to obtain a homogenous metal gel. Since the silver compound is highly photosensitive, the particle-free metal gel paste was kept in an opaque or amber bottle under refrigerated conditions. The results are shown in Table 2.

[0110] [Table 2]

[0111] The metal content of the metal gel can be varied by varying the weight percentage of the silver precursor in the formulation.

[0112] Example 1-III: 12 g of silver neodecanoate was weighed into a two-neck round bottom flask equipped with a thermometer and a condenser. To the silver precursor, 2.25 g of terpineol and 2.25 g of trigol were added. The reaction mixture was then heated at 85° C. with constant stirring until all the silver neodecanoate was completely dissolved. The resulting mixture was then allowed to cool and then crushed to obtain a homogenous metal gel. The metal gel was kept in an amber bottle under refrigerated conditions. The results are shown in Table 3.

[0113] [Table 3]

[0114] Example 1-IV: 12 g of silver neodecanoate was weighed into a two-neck round bottom flask equipped with a thermometer and a condenser. To the silver precursor, 2.25 g of terpineol and 2.25 g of 2-methyl-1,3-propanediol were added. The reaction mixture was then heated at 85° C. with constant stirring until all of the silver neodecanoate was completely dissolved. The resulting mixture was then allowed to cool and then ground to obtain a homogenous metal gel. The results are shown in Table 4.

[0115] [Table 4]

[0116] (2) Synthesis of metal-organic paste: Example 2-I: 9.2g of Silver Neodecanoate was weighed into a container. 2.25g of Triethylene Glycol was added to it. The mixture was then mixed in a planetary mixer at 1000 rpm for 1 minute. The slurry was then milled to obtain a homogenous paste. The paste was kept in an amber bottle in refrigerated condition. The results are shown in Table 5.

[0117] [Table 5]

[0118] Metal gel and its form factor: Thermal Characterization: Thermogravimetric analysis (TGA) of the particle-free molecular paste or metal gel showed complete evaporation of the solvent and decomposition of the metal-organic precursor below 250°C. The total weight loss of 72% at 250°C reveals the fact that upon heating the metal gel at 250°C, the organic moiety is completely detached from elemental silver and evaporated leaving no carbon residue, but only bulk silver metal. Thus, the thermal decomposition of the silver precursor leads to the deposition of only pure silver metal without any carbon residue. At temperatures above 250°C, the TGA residue percentage is close to the theoretical weight percentage of silver in silver neodecanoate (28 wt%) based on the chemical formula. This clearly indicates that the thermal decomposition of silver neodecanoate occurs completely leaving only pure silver.

[0119] Differential scanning calorimetry (DSC) of the particle-free metal gel shows an endothermic peak at 100-120 °C, indicating melting of the silver neodecanoate isomers along with slow evaporation of the solvent. The silver neodecanoate isomers undergo a solid-to-liquid phase transition before thermal decomposition, which occurs above 200 °C. Two exothermic peaks at 205 and 228 °C in the DSC indicate that the decomposition of the silver precursor is a two-stage decomposition process.

[0120] Paste Viscosity and Stability: The viscosity of the paste was measured using a Brookfield viscometer (HB DV-lll) Spindle CP51 at 1 rpm. The viscosity of the paste was 76 Pa.s. The viscosity was measured every other day. There was no change in the viscosity of the paste one month after preparation, indicating good stability of the paste.

[0121] Particle-free molecular paste or metal gel; form factor and its application in die attach: (i) Printing paste and its application in die attach: Attachment of semiconductor or other die elements can be achieved by printing metal gel or particle free molecular paste on substrates such as DBC (Direct Bonded Copper), DPC (Direct Plated Copper), MCPCB (Metal Core PCB), FR4, Copper Lead Frame, Flexible PCB, etc. with the aid of DEK printer.

[0122] The printed substrate was dried at 180 °C for 60 min in air. The pre-dried material was then allowed to cool at normal room temperature. Our studies showed that the pre-dried printed material does not contain any organic impurities resulting from the decomposition reaction of the metal precursors. Complete removal of organic impurities before die placement provides a carbon-free joint between the die and the substrate. Die elements such as gold-coated Si die and Ag ribbon were placed on the pre-dried printing area. The assembly was then wrapped in aluminum foil. The vehicle was then subjected to 260 °C for 1 min at a pressure of 10 MPa in a Carver press.

[0123] The assembled sample was then subjected to X-ray analysis for void measurement. X-ray of the assembled sample showed less than 1% voids. The low voids can be attributed to wetting of the die and substrate surfaces due to the transition from solid to liquid phase before decomposition of the silver precursor.

[0124] Figures 1a and 1b show FESEM micrographs of cross-sections of assembled samples. The SEM cross-sections show good densification of the silver. The SEM cross-sections also reveal good diffusion of silver onto the die and also onto the substrate interface, which is of course a contributing factor to the higher bond strength. The measured bond line thicknesses vary from 2.5 microns to 3 microns.

[0125] The bond strength of the assembled samples was evaluated using a DageDie shear. *A 3 mm Au coated Si die exhibits a bond strength of over 50 MPa. The die shear values ​​could not be accurately quantified because part of the die shattered and most of the die adhered to the substrate. Data was also collected for a high temperature die shear performed at 260°C. It was found that there was no degradation in bond strength when the die shear was performed at the higher temperature.

[0126] The bond strength was further evaluated by measuring the peel strength of Ag ribbons (2 mm wide and 85 microns thick) attached to gold-coated DBC substrates using an IMADA peel tester. The obtained peel strength was much stronger than the joints made with reported nanoparticle-based interconnect materials. The failure mode of the joints shows bulk failure. Microscopic images (Figures 2a and 2b) show a diffuse layer of silver on both the silver ribbon and DBC sides.

[0127] The microstructure of the silver diffused layer on both interfaces was analyzed using FESEM. The FESEM micrographs (Figures 3a and 3b) show the diffused silver layer on the surface of the ribbon and DBC with elongated spike-like structures. This reveals the fact that peeling the ribbon from the substrate created large stresses in the diffused silver layer of the ribbon and DBC, which caused the silver layer to protrude from the surface.

[0128] The assembled specimens were subjected to 3000 and 1000 cycles of thermal shock testing (+150 to -50 °C with 3 min dwell time). X-ray analysis shows that the porosity slowly increases from 0.3% to 1% with an increasing number of thermal shock cycles (Figures 4a, 4b, and 4c).

[0129] After completing 3000 cycles, it was observed that there was no degradation in the die shear strength. During die shear failure, it was found that most of the die was crushed and attached to the substrate after 3000 cycles, revealing excellent bond strength. Figures 5a, 5b, and 5c show FESEM cross sections of 3000TS. The cross sections reveal good diffusion of the silver layer at both interfaces with no cracks in the silver layer and interfaces.

[0130] Our studies show that with increasing sintering pressure and sintering time, the peel strength increases. For low pressure die attach, higher bond strength can be achieved by increasing the sintering time. In our case, a maximum of 20 N / mm can be achieved at 10 MPa for 1 minute at 300°C. Table 6 shows the peel strength at different sintering pressures and temperatures.

[0131] [Table 6]

[0132] (ii) Free-standing silver film / foil and its application in die attachment: Preparation of free-standing silver films: The particle-free molecular paste was printed on a glass substrate. The printed glass substrate was then heated at 150°C for 140 minutes. It was then cooled at room temperature. The glass substrate was then immersed in a water bath for 10 minutes. This allows the print to be detached from the glass. The thin silver film was then dried at room temperature for 60 minutes. The thickness of the silver film varies depending on the thickness of the stencil. Essentially, silver films with thicknesses varying from 3 microns to 15 microns were synthesized. The synthesized silver films were flexible and these films were further used for die attach applications.

[0133] The synthetic film can be used as a die attach interconnect material. * A 3 mm Au-coated Si die was placed as an interconnect material between the substrate (gold-coated DBC). The assembled sample was then wrapped in aluminum foil and then subjected to 260 °C for 1 min at 6 MPa pressure in a Carver press. X-ray analysis showed that the assembled sample did not show the presence of any voids.

[0134] The resulting die shear was about 40 MPa. The resulting failure mode was interfacial failure. A diffused layer of silver was observed on the die side, but no silver layer was observed on the substrate side.

[0135] Its applications in wafer stacking and die attach: The particle-free molecular paste was printed onto Au-coated 2'' silicon wafers using a DEK printer. The printed wafers were then dried at 180 °C for 75 min in a box oven. The stacked wafers were then attached to UV tape and diced using an ADT7100 dicing machine. The coated singulated die was then used for die attach on the Au-coated DBC using a Datacon die bonder. The UV tape did not show any remnants of the silver coating on the UV tape. The coated Si die was then attached to the DBC substrate at 250 °C for 1 min using a sintering pressure of 6 MPa.

[0136] X-ray analysis revealed the presence of 0.3% voids. The bond strength of the assembled specimens at 250°C and 6 MPa sintering pressure was approximately 40 MPa. Failure mode analysis of the assembled specimens indicated bulk failure.

[0137] Metal organic paste, die attach applications: The metal-organic paste of the present invention was printed onto the DBC. The printed substrate was dried at 180°C for 60 minutes. The pre-dried material was then allowed to cool at normal room temperature. Die elements such as gold-coated Si die and Ag ribbon were placed on the pre-dried printing area. The assembly was then wrapped in aluminum foil. The vehicle was then subjected to 260°C for 1 minute at 10 MPa pressure in a Carver press. The bond strength of the assembled samples was evaluated using a DageDie shear. The assembled 3mm *The 3 mm Au coated Si die shows a bond strength of over 50 MPa. The die shear value could not be accurately quantified because part of the die shattered and most of the die was attached to the substrate. The bond strength was further evaluated by measuring the peel strength of an Ag ribbon (2 mm wide and 85 microns thick) attached to the gold coated DBC substrate using an IMADA peel tester. The resulting peel strength was about 8-10 N / mm. The failure mode of the bond shows bulk failure as shown in Figure 6a and Figure 6b.

[0138] Soldering on Silver Metal Gel: This disclosure also reveals soldering on metal gel. The metal gel of the present invention has been found to have 5B loading on PI, PET, FR4, glass, ceramic, metal and polymer substrates. In the present invention, the metal gel was printed on the FR4 / polyimide substrate, which was then cured at 180°C for 1 hour. On the printed surface of the metal gel, (Sn / Bi) solder paste was printed and reflowed under nitrogen / air. Good wetting properties of the solder on the printed metal gel on the polymer substrate were observed (see Figures 9a-c).

[0139] The soldered assembly was cross-sectioned for FESEM micrographs. From Figures 7a, 7b, and 7c, it can be easily seen that the solder paste has diffused well through the metal gel layer and no cracks are visible at the solder and gel interface. EDAX performed at the interface shows approximately 70% Ag and 30% (wt / wt) Sn. The composition ratio clearly reveals the formation of Ag3Sn.

[0140] (3) Synthesis of copper metal gel: Example 3-I: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 0.03 g of silver neodecanoate and 1 g of glycerol were added to the previous mixture, which was then mixed for 2-3 minutes. The entire mixture was then ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0141] Example 3-II: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 0.7 g of glycerol and 0.3 g of diethylene glycol monomethyl ether were added to the previous mixture, which was then mixed for 2-3 minutes. The entire mixture was then ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0142] Example 3-III: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 1 g of terpineol was added to the previous mixture, which was then mixed for 2-3 minutes. The entire mixture was then ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0143] Example 3-IV: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 1 g of glycerol was added to the previous mixture, which was then mixed for 2-3 minutes. After that, the entire mixture was ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0144] Example 3-V: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 0.5 g of glycerol was added to the previous mixture, which was then mixed for 2-3 minutes. After that, the entire mixture was ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0145] Example 3-VI: 4.5g of copper(II) formate tetrahydrate was weighed out and 0.2g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 0.5g of Cu nanopowder and 1g of glycerol were added to the previous mixture, which was then mixed for 2-3 minutes. After that, the entire mixture was ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 10 minutes.

[0146] Example 3-VII: 8 g of silver metal gel (see section (1) of the experimental section) and 2 g of Example 3-IV were weighed out and then mixed and homogenized using an orbital mixer at 1000 RPM for 1 minute three times.

[0147] Examples 3-VIII: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 1 g of glycerol and 0.31 g of 1-ethyl-2-pyrrolidinone were added to the previous mixture, which was then mixed for 2-3 minutes. The entire mixture was then ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 1 minute.

[0148] Example 3-IX: 5 g of copper(II) formate tetrahydrate was weighed out and 0.2 g of 3-(dimethylamino)-1,2-propanediol was added to it. This mixture was then heated at 130°C for 10 minutes with occasional stirring, and then it was cooled to room temperature. After that, 1 g of 1-ethyl-2-pyrrolidinone was added to the previous mixture, which was then mixed for 2-3 minutes. The entire mixture was then ground in a three-roll mill, and then it was homogenized in an orbital mixer at 1000 RPM for 1 minute.

[0149] Copper Gel, Die Attach Applications: Copper gel was printed onto the DBC. The printed substrate was then dried at 160°C for 30 minutes in a nitrogen atmosphere. The pre-dried material was then allowed to cool at room temperature. A die element, such as a gold-coated Si die, was placed onto the pre-dried print area. The assembly was then wrapped within an aluminum foil with a graphite sheet for a cushioning effect. The vehicle was then subjected to 260°C for 2 minutes at a pressure of 10 MPa in a Carver press. The bond strength of the assembled samples was evaluated using a DageDie shear. The assembled 3 mm * The 3 mm Au-coated Si die exhibits a bond strength of over 70 MPa. The die shear value could not be quantified precisely because part of the die shattered and most of the die was attached to the substrate.

[0150] FESEM micrographs (Figures 8a-e) of cross sections of assembled samples show good densification of copper. SEM cross sections also reveal good diffusion of copper onto the die and substrate interfaces, which is not surprising as a contributing factor to higher bond strength. Bond line thickness for printing using a 200 micron stencil is approximately 11 microns.

[0151] Soldering on copper metal gel: The metallic copper gel of the present invention has been found to have good addition to PI, PET, and FR4 substrates when laminated at 150-200°C with a minimum pressure of 5MPa. In the present invention, the copper gel is printed onto the FR4 / polyimide substrate, which is then pre-dried at 160°C for 30 minutes under nitrogen, and then laminated in a Carver press at 200°C (PI and FR4) / 150°C (PET) for 2 minutes with a pressure of 5MPa. On the laminated surface of the metallic copper gel, solder paste was printed and reflowed under nitrogen. Good wetting properties of the solder on the metallic copper gel printed onto the polymer substrate were observed. When 1026 parts were soldered, the joint strength was 4-5kg with bulk failure.

[0152] The foregoing detailed description has been provided by way of illustration and description and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments described herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.

[0153] The invention will now be described with reference to the following numbered clauses: 1. A sintered composition comprising: Solvent, and A sintering composition comprising: a metal complex dissolved in a solvent. 2. A sintering composition according to clause 1 in the form of a gel, preferably a metal gel. 3. A sintering composition according to claim 1 or 2, wherein the sintering composition is for die attachment. 4. A sintering composition according to any one of clauses 1 to 3, wherein the solvent is supersaturated with the metal complex. 5. A sintered composition according to any one of clauses 1 to 4, wherein the sintered composition is substantially free of polymers, preferably substantially free of organic polymers. 6. A sintering composition according to any one of clauses 1 to 5, wherein the sintering composition is substantially free of metal particles and / or substantially free of particles of metal complexes. 7. The sintering composition according to any one of clauses 1 to 6, wherein the metal complex comprises an organometallic complex. 8. The sintering composition according to clause 7, wherein the metal of the organometallic complex is selected from one or more of Ag, Au, Pt, Pd, Ni, Cu and Mo, preferably Cu and / or Ag. 9. The sintered composition according to any one of clauses 1 to 8, wherein the metal complex comprises silver neodecanoate. 10. A sintering composition according to any one of clauses 1 to 9, wherein the solvent has a boiling point of less than 300°C, preferably less than 250°C, more preferably less than 200°C. 11. The sintered composition according to any one of clauses 1 to 10, wherein the metal complex substantially decomposes at a temperature of less than 300°C, preferably less than 250°C, more preferably less than 200°C. 12. A sintering composition according to any one of clauses 1 to 11, wherein the sintering composition comprises a metal complex in an amount of 60% by weight or more, preferably 70% by weight or more, more preferably 75% by weight or more, based on the total weight of the sintering composition. 13. A sintering composition according to any one of clauses 1 to 12, wherein the sintering composition comprises at least 20% by weight metal, preferably at least 25% by weight metal, more preferably at least 30% by weight metal, and even more preferably at least 35% by weight metal, based on the total weight of the sintering composition. 14. The sintering composition according to any one of claims 1 to 13, wherein the solvent comprises an organic solvent, preferably the solvent is selected from one or more of propane-1,2-diol, terpineol, trigol, or 2-methyl-1,3-propanediol, preferably terpineol. 15. A sintering composition according to any one of claims 1 to 14, wherein the viscosity of the sintering composition is 70,000 to 80,000 cP. 16. A sintered composition according to any one of clauses 1 to 15, wherein the sintered composition is substantially free of metal oxides. 17. A sintering composition according to any one of clauses 1 to 16 in the form of a free-standing film or foil, and / or laminated onto a wafer. 18. A sintering paste comprising: Solvent, and A sinter paste comprising: a metal complex suspended in a solvent. 19. A sintering paste according to clause 18, comprising a sintering composition according to any one of clauses 1 to 17. 20. A sintering paste according to clause 18 or 19, wherein the solvent comprises triethylene glycol. 21. A sintering paste according to any one of clauses 18 to 20, wherein the metal complex is present in an amount of 70% by weight or more, preferably 80% by weight or more, based on the total weight of the sintering paste. 22. A sintering paste according to any one of clauses 18 to 21, wherein the sintering paste is for die attachment. 23. A sintering paste according to any one of clauses 18 to 22 in the form of a free-standing film or foil and / or laminated onto a wafer. 24. A method for producing a sintered composition according to any one of claims 1 to 17, comprising: at least partially dissolving a metal complex in a solvent to form a solution; and milling the solution. 25. The method according to claim 24, wherein the dissolution is carried out at a temperature between 60°C and 100°C, preferably between 70°C and 80°C. 26. The method according to claim 24 or 25, wherein the solution is cooled before grinding. 27. A method for producing a sintering paste according to any one of clauses 18 to 23, comprising: Providing a slurry comprising a metal complex and a solvent; and milling the slurry. 28. Use of a sintering composition according to any one of clauses 1 to 17 and / or a sintering paste according to any one of clauses 18 to 23 in a method selected from die attachment, wafer-to-wafer bonding, hermetic and near-hermetic seals, dispensing, and generation of interconnect lines. 29. A method of forming a joint between two or more work pieces, comprising the steps of: providing two or more work pieces to be joined; providing a sintering composition according to any one of clauses 1 to 17 and / or a sintering paste according to any one of clauses 18 to 23 adjacent to two or more work pieces; and heating the sintering composition and / or sintering paste to at least partially evaporate the solvent. 30. The method of claim 29, wherein the solvent is substantially evaporated, preferably the solvent is completely evaporated. 31. The method according to claim 29 or 30, wherein at least a portion of the metal complexes of the sintering composition and / or sintering paste decomposes, preferably substantially all of the metal complexes of the sintering composition and / or sintering paste decomposes. 32. The method according to any one of clauses 29 to 31, wherein the heating is carried out at a temperature of less than 300°C, preferably less than 270°C, more preferably less than 250°C, and most preferably less than 230°C. 33. The method of any one of clauses 29-32, wherein heating results in a substantially carbon-free joint. 34. The method of any one of clauses 29 to 33, wherein the metal of the metal complex is at least partially sintered. 35. A sintered joint formed using a sintering composition according to any one of clauses 1 to 17 and / or a sintering paste according to any one of clauses 18 to 23, preferably wherein the sintered joint is formed using a method according to any one of clauses 29 to 34. 36. A sintered joint as described in clause 35, wherein the joint is substantially free of solvents, and preferably substantially free of carbon. 37. A sintered joint according to clause 35 or 36, wherein the joint is substantially free of metal complexes.

Claims

1. 1. A sintered composition comprising: A solvent; a metal complex dissolved in said solvent; The sintering composition contains at least 75 wt. % of the metal complex, based on the total weight of the sintering composition; and A sintering composition, the sintering composition comprising at least 20 wt. % metal, based on the total weight of the sintering composition.

2. 2. The sintering composition of claim 1, comprising the solvent and the metal complex dissolved in the solvent.

3. 3. The sintered composition of claim 1 or 2, wherein the metal complex substantially decomposes over a temperature range of less than 20°C.

4. The sintering composition according to any one of claims 1 to 3, wherein the solvent is supersaturated with the metal complex.

5. 5. The sintered composition according to claim 1, wherein the sintered composition contains at least 25% by weight of metal, based on the total weight of the sintered composition.

6. The sintered composition according to any one of claims 1 to 5, wherein the metal complex substantially decomposes at a temperature of less than 200°C.

7. The sintering composition according to any one of claims 1 to 6, wherein the solvent and / or the ligand of the metal complex have a boiling point of less than 300°C.

8. 8. The sintered composition according to claim 1, wherein the metal of the metal complex is selected from one or more of silver, gold, platinum, palladium, nickel, copper, and molybdenum.

9. 9. The sintering composition according to claim 1, wherein the solvent comprises an organic solvent, the solvent being selected from one or more of propane-1,2-diol, terpineol, triethylene glycol, glycerol, and 2-methyl-1,3-propanediol.

10. The metal complex has the structure RCOO - 10. The sintering composition according to claim 1, wherein R is a branched or unbranched hydrocarbon chain having up to 14 carbon atoms.

11. The sintered composition according to any one of claims 1 to 10, wherein the metal complex is selected from one or more of silver neodecanoate, silver 2-ethylhexanoate, silver oxalate, silver lactate, silver hexafluoroacetylacetonate cyclooctadiene, copper formate tetrahydrate, and copper acetate.

12. 12. The sintered composition according to claim 1, wherein the viscosity of the sintered composition is from 60,000 to 120,000 cP.

13. The sintered composition is Gel, or a free-standing film or foil, or Coating, depositing, printing, or laminating on a wafer, or 13. The sintered composition according to any one of claims 1 to 12, in the form of coating, depositing, printing or laminating on a substrate made of glass and / or ceramic and / or metal and / or polymer film and / or composite material used as a printed circuit board.

14. A method for producing a sintered composition according to any one of claims 1 to 13, comprising the steps of: Providing a solvent; Providing a metal complex; and dissolving said metal complex in said solvent at a temperature between 100° C. and 180° C. to form a solution.

15. The method of claim 14 , wherein the solution is supersaturated.

16. 16. The method of claim 14 or 15, further comprising cooling the solution to a temperature of 30 to 60°C.

17. The method of any one of claims 14 to 16, wherein the method further comprises milling the solution.

18. The method of any one of claims 14 to 17, wherein dissolving the metal complex in the solvent is carried out at a temperature of from 110°C to 150°C.

19. The method according to any one of claims 14 to 18, wherein the sintering composition does not comprise any metal particles and / or does not comprise any particles of the metal complex.

20. 1. A method for forming a sintered metal deposit on a substrate, comprising: Providing a substrate; disposing a sintered composition according to any one of claims 1 to 13 on the substrate; drying the composition at a temperature of 140-200° C. to form a dry composition; Sintering the dried composition at a temperature of 150°C to 300°C; A method wherein said sintering is carried out at a temperature higher than said temperature of said drying.

21. 21. The method of claim 20, wherein the substrate comprises one of PET, PC, PI, TPU, PEN, and PEEK.

22. The substrate is made of FR4, glass, and Al. 2 O 3 , SiC, or SiO 2 21. The method of claim 20, comprising: a ceramic such as; a semiconductor material such as Si, SiC, Ge, or GaN; or a metal foil such as a metal foil formed of Cu, Ag, Au, Al, Ni, or an alloy.

23. The method of any one of claims 20 to 22, wherein disposing the sintering composition on the substrate comprises stencil printing and / or screen printing the sintering composition onto the substrate.

24. 24. The method according to any one of claims 20 to 23, wherein the metal complex of the sintering composition comprises silver and the drying is carried out at a temperature of 170°C to 190°C for 30 to 90 minutes.

25. 24. The method according to any one of claims 20 to 23, wherein the metal complex of the sintering composition comprises copper and the drying is carried out at a temperature of 150°C to 170°C for 15 to 60 minutes under a nitrogen atmosphere.

26. The method according to any one of claims 20 to 25, wherein the sintering is carried out at a temperature between 180°C and 295°C.

27. A method according to any one of claims 20 to 26, wherein the sintering step is carried out at a pressure between 2 MPa and 15 MPa.

28. The method of any one of claims 20 to 27, wherein the sintered metal deposit comprises a bond between a die and a substrate.

29. The method of any one of claims 20 to 27, wherein the sintered metal deposit comprises an electrical circuit or interconnect.

30. The method of any one of claims 20 to 27, wherein the sintered metal deposit comprises a coating.

31. 31. The method of any one of claims 20 to 30, wherein the sintered metal deposit is substantially free of metal complexes, and / or substantially free of organic ligands, and / or substantially free of organic material, and / or substantially free of carbon.

32. A method according to any one of claims 20 to 31, wherein the sintered metal deposit has a die shear strength of at least 30 MPa.

33. 33. The method of any one of claims 20 to 32, wherein the porosity in the sintered metal deposit is less than or equal to 0.5% after 1000 cycles of thermal shock testing from +150°C to -50°C with a dwell time of 3 minutes.

34. 34. The method of any one of claims 20 to 33, wherein the porosity in the sintered metal deposit is less than or equal to 1.5% after 3000 cycles of thermal shock testing from +150°C to -50°C with a dwell time of 3 minutes.

35. A method according to any one of claims 20 to 34, wherein the peel strength of the sintered metal deposit is 10 N / mm or more.

36. A method according to any one of claims 20 to 35, wherein the sintered metal deposit is solderable and / or high current capable.

37. A method according to any one of claims 20 to 36, wherein the sintered metal deposit is flexible.

38. A method according to any one of claims 20 to 37, wherein the sintered metal deposit exhibits a sheet resistance of less than 12 mΩ / sq / mil.

39. 1. A method of die attachment comprising the steps of: Providing a substrate and a die; disposing a sintered composition according to any one of claims 1 to 13 between the substrate and the die; drying the composition at a temperature of 140-200° C. to form a dry composition; sintering the dried composition at a temperature of greater than 150° C. to 300° C. and a pressure of 2 MPa to 15 MPa to attach the die to the substrate; A method wherein said sintering is carried out at a temperature higher than said temperature of said drying.

40. The method of claim 39, wherein the sintering is carried out at a pressure of between 4 MPa and 12 MPa.

41. 1. A method for forming electrical circuits or interconnections on a substrate, comprising: Providing a substrate; disposing the sintered composition according to any one of claims 1 to 13 on the substrate in the form of a circuit or interconnect; drying the composition at a temperature of 140-200° C. to form a dry composition; sintering the dried composition at a temperature of 150° C. to 300° C. to form the circuit or interconnect; A method wherein said sintering is carried out at a temperature higher than said temperature of said drying.

42. 42. The method of claim 41, wherein the substrate is either rigid or flexible.

43. 1. A method for manufacturing a soldered assembly, comprising: Producing a sintered metal deposit on a substrate according to a method according to any one of claims 20 to 38; depositing a solder paste onto the sintered metal; contacting a component with the deposited solder paste; and reflowing the solder paste to provide a soldered assembly.

44. 44. The method of claim 43, wherein the component is selected from an electronic component, an LED, a metallized printed circuit board, and a heat sink.

45. 45. The method of claim 43 or 44, wherein the substrate is selected from a carrier film, an interposer, or a circuit board or a heat sink.

46. Use of the sintered composition according to any one of claims 1 to 13 in a method selected from die attachment, wafer-to-wafer bonding, hermetic and near-hermetic sealing, dispensing, and producing circuitry or interconnect lines.

47. Use of the sintered composition according to any one of claims 1 to 13 in the method according to any one of claims 20 to 38 for producing electric / electronic devices, interconnects, assemblies, circuits, or printed cables and wire harnesses.

48. 48. Use of a sintered composition according to claim 47, wherein said assemblies and / or circuits are flexible or thermoformed and / or injection molded 3D electronic structures.

49. 49. Use of a sintered composition according to claim 47 or 48, wherein the assembly and / or circuit is solderable and capable of carrying high current densities.

Citation Information

Patent Citations

  • Low temperature ag-compositions

    EP3085811A1

  • Metal nanoparticle paste, and pattern forming method

    JP2009099518A

  • Metal nanoparticle paste and conductive base material

    JP2010177084A

  • Multi-layer composite with metal-organic layer

    JP2014141071A